Maintaining Public Trust and Reputation in the Digital Age - Kuswati, Yeti; Kusmayadi, Dody; Pratomo, Herdianto Wahyu (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
The evolution of digital technology and social media has significantly transformed the landscape of public communication. Public trust and institutional reputation have become strategic elements for organizational sustainability amidst the torrent of information and disinformation. This article aims to analyze the key factors in maintaining public trust and institutional reputation in the digital age and to formulate effective strategies based on current literature and case studies. A qualitative-descriptive approach was used, with data sources derived from scientific literature reviews and public case documentation. The analysis results indicate that transparency, accountability, digital literacy, rapid crisis response, and data-driven communication management are the primary foundations for maintaining trust and reputation sustainably. This study provides conceptual and practical contributions to strengthening public communication governance in the digital age.